Second Language Learner Attitudes Towards Peer Use of a Variable Sociophonetic Cue - Elena Schoonmaker-Gates (Languages, 2025)
Studies that have examined /s/ weakening as a social practice have found that L1 Spanish speakers perceive this cue as an indicator of lower status, region of origin, and greater friendliness, and even L2 Spanish learners have been found to associate /s/ weakening with lower status. The question remains, however, whether L2 learners who use /s/ weakening are perceived as having these same social attributes or whether their nonnative status interrupts said assessment. The present study examines the attitudes of 30 beginning and intermediate-level L2 learners of Spanish towards L1 and L2 speech that was digitally modified to contain /s/ deletion in coda positions, a regionally and stylistically variable sociophonetic cue in Spanish that is often not adopted by L2 learners. Participants rated the speech samples on Likert scales of perceived status, solidarity, and nativeness. Results revealed that learners rated L1 speech with /s/ deletion significantly lower for status and L2 speech with /s/ deletion significantly higher for nativeness.